Building common understanding - Muhl, Caitlin (2024)
Funding Information: This report is independent research supported by the National Institute for Health and Care Research Applied Research Collaboration South West Peninsula. The views expressed in this publication are those of the authors and not necessarily those of the National Institute for Health and Care Research or the Department of Health and Social Care. This report is independent research supported by the Dalla Lana School of Public Health at the University of Toronto. The views expressed in this publication are those of the authors and not necessarily those of the Dalla Lana School of Public Health or the University of Toronto. Publisher Copyright: © The Author(s) 2024.